(untitled) (Journal of Medicine, 2022)
Background: The health care workers’(HCWs) are working 24/7 in managing devastating pandemicCorona virus disease19(COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARSCoV-2) as front liner which leads them to be at highest risk for contacting infection. In Bangladesh, beinga lower middle-income country and densely populated, the burden is much more on HCWs. Methods: We did a cross-sectional study with an aim to identify the prevalence, risk factors, and outcomesof SARS-CoV-2 infection among the HCWs in a COVID-19 dedicated tertiary care hospital. Statisticalanalysis was done in SPSS version-26. Multivariate regression analysis was done to evaluate risk factorsresponsible for COVID-19 infection and the severity of the COVID-19 disease. We expressed odds ratiowith 95% CI, and considered the p-value of <0.05 as significant in the two-tailed test. Results: A total of 864 HCWs had participated with mean age of 34.16 ± 6.77 and 426 (49.31%) males.Among them 143 (16.55%) were tested RT-PCR positive for SARS-COV-2. Bronchial asthma/COPD andHypertension were the most common co-morbidities with 23 (16.08%) for each. About 102 (71.33%) ofthe RT-PCR positive HCWs became symptomatic. Fever, cough and myalgia were the most commonsymptoms 84(82.35%), 67(65.69%) and 52(50.98%) respectively.Multivariate regression analysis revealed hypertension, gout, and working in the COVID-19 confirmedward had a significant odds ratio for getting infected with SARS-CoV-2 [95% CI, p-value 1.91 (1.08 - 3.41),0.027; 5.85 (1.33 - 25.74), 0.020; and 1.83 (1.10 - 3.03), 0.019].Bronchial asthma/COPD and gout found to be risk factors for moderate to severe COVID-19 disease[95% CI, p-value 3.04 (1.01 - 9.21), 0.049 and 23.38 (3.42 - 159.72), 0.001]. Hospitalization rate was12(85.7%), and 3(100%) and median hospital stays were 11 (5.5 - 15), and 20 (7 - 30) days for moderate andsevere diseases respectively. Outcome was uneventful without any ICU admission and death. Conclusion: HCWs working in the COVID-19 confirmed ward are at increased risk of infection withSARS-COV-2. Some co-morbidities like hypertension and gout are important risk factors for contactingSARS-COV-2 infection. Bronchial asthma/COPD and gout favors disease severity. J MEDICINE 2022; 23: 5-12